Non-line-of-sight outdoor channel identifcation for wireless sensor networks based on impluse radio ultra wide band - Anouar Darif; Rachid Fateh (Institute of Advanced Engineering and Science, 2022)
Wireless sensor networks (WSN) have become increasingly popular in a variety of fields in recent years. This is due to the development of their capabilities, which include remote environmental monitoring, process automation, telemedicine, and many other domains. Besides, among the widely used modern WSN radio technologies, we find impluse radio ultra wide band (IR-UWB) that is recognized by their advantages regarding low power consumption, low cost, low complexity and high resistance to multipath fading in outdoor wireless networks. Energy consumption minimization, packet delivery ratio improvement and latency minimization are the main objectives in this work. The chosen performance metrics (energy consumption, packet delivery ratio and latency) are justified by the direct impact of these three parameters on the network’s efficiency. Accordingly, we proposed and introduced an outdoor non-line-of-sight (NLOS) packet delivery ratio using broadband radio access network (BRAN) channel to improve WSN’s based on IR-UWB performance in terms of energy consumption, packets delivery ratio (PDR) and latency.